Polarized Th2 cells attenuate high-fat-diet induced obesity through the suppression of lipogenesis - Lijun Dong; Jingtao Gao; Lu Yu; Shibo Liu; Yuxin Zhao; Wen Zhang; Yinming Liang; Hui Wang (BMC Immunology, 2024)
Abstract Immune cells, such as macrophages, B cells, neutrophils and T cell subsets, have been implicated in the context of obesity. However, the specific role of Th2 cells in adipose tissue function has remained elusive. Eight-week-old male CD3ε─/─ mice were randomly divided into two groups (≥ 5 mice per group): one received intravenous injection of Th2 cells isolated from LATY136F mice, while the other receiving PBS as a control. Both of groups were subjected to a high-fat diet (HFD). The adoptive transfer of polarized Th2 cells led to a significant reduction in obesity following a HFD. This reduction was accompanied by improvements in hepatic steatosis, glucose intolerance, and insulin resistance. Mechanistically, Th2 cell treatment promoted oxidative phosphorylation of adipocytes, thereby contributing to a reduction of lipid droplet accumulation. These findings suggest that Th2 cell therapy represents a novel approach for treating diet-induced obesity and other diseases involving lipid droplet accumulation disorders.